Sistem Pendukung Keputusan Pemilihan JSK di Ramayana Menerapkan Metode DEMATEL dan ARAS - Nova Yanti Saragih (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
JSK(Junior Supervisor cashier) is a person who has good experience, knowledge and skills to lead and manage finances every day. JSK also plays a role in regulating and coordinating cashiers on duty, starting from managing shifts, taking capital, and minimizing losses caused by cashiers. Decision Support System is a computer-based system consisting of several components, namely language system components, knowledge system components, and problem processing system components that are interrelated with one another, in making decisions through the use of data. -data and decision models in order to solve a problem. DEMATEL (Decision Making Trial And Evaluation Laboratory) aims to find direct (dependency) in a system of variables. The Additive Ratio Assessment (ARAS) method is a method used for ranking criteria, in carrying out the ranking process, the ARAS method has several steps that must be done to calculate and this method is very suitable for use in the selection of JSK candidates where the highest value is the best value of the final result